A parallel exponential integrator scheme for linear differential equations - Hecht, F.; Kaber, S.-M. (Applied numerical mathematics, 2025)
New approximations of the matrix φ functions are developed. These approximations are rational functions of a specific form allowing simple and accurate schemes for linear systems. Furthermore, these approximations are fully parallelizable. Several tests show the efficiency of the method and its good parallelization properties.